Social Media Capabilities dalam Adopsi Media Sosial Guna Meningkatkan Kinerja UMKM - Lia Febria Lina; Berlintina Permatasari (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2020)
Social media is currently being used by both large companies and SMEs. For large companies the use of social media has been used successfully in reaching potential consumers. However, for SMEs, the marketing strategy of using social media is still being questioned. The purpose of this study is to fill the gaps in previous research by examining the driving factors for SMEs in using social media in promoting their products and testing how the performance of SMEs after adopting this technology is good both in financial and non-financial aspects that have not been done much research. The results of this study found that the compatible, cost-effective, interactive variables had a positive effect on the use of social media and subsequently had a positive effect on both financial and non-financial performance. However, the moderating role of social media capabilities cannot strengthen the relationship between use and the performance of SMEs. The results of this study are expected to be the basis for evaluating SMEs so that they can use digital media to support their business. The government must also pay attention to this to actively socialize the use of digital media for MSMEs so that the performance of SMEs can increase.